Pelatihan Desain Kemasan untuk Meningkatkan Kapasitas Ibu Rumah Tangga dalam Pengembangan Produk Pembersih di Desa Karya Indah - Imelda Yunita; Ayu Diana; Erpiani Siregar; Fikratul Ihsan; Resdati Resdati; Rahmayuni Rahmayuni; Muhammad Zakiyul Fikri (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2026)
Packaging design is an important aspect of enhancing the attractiveness and market value of products, Packaging design plays an important role in increasing the attractiveness and selling value of a product. This community service activity aims to improve the ability of housewives in Karya Indah Village, Apung District, Kampar Regency, in designing packaging for dishwashing soap and floor cleaner. The activity was carried out through socialization, education, demonstration, and direct practice using the Canva and PixelLab applications based on Android. The material covers the function of packaging as a visual communication medium, basic design principles, color selection, arrangement of product information, and making packaging stickers. The results of the activity showed that participants actively took part in the training and were able to produce more attractive and informative packaging designs. This training also increased participants' understanding of the role of packaging in supporting marketing and product competitiveness. This activity successfully improved the knowledge and skills of partners in designing packaging and supported the development of household businesses.